Health Promotion Theory - Davies, Maggie (Executive director); Macdowall, Wendy (Maidenhead : Open University Press, 2006)
This text will provide readers with a sound understanding of the theory of health promotion, enabling them to develop the skills needed to translate theory into practice at the level of public policy develompent and implementing and evaluating intervetions.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Health promotion; Health Promotion